Cross-Country Report on Minimum Wages : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper provides a cross-country report on minimum wages. In the past few years, many countries in Central Eastern and Southeastern Europe (CESEE) have increasingly turned to minimum wage policies. Throughout the region, statutory minimum wages had been in place at least since the early 1990s, but they were typically set at relatively moderate levels and affected relatively few workers. Minimum wages have risen sharply relative to both average wages and labor productivity. Minimum wages often affect relatively more workers in CESEE than in Western Europe. Governments are the key players in the minimum wage determination in CESEE countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet